Water, sanitation and hygiene (WASH) and biosecurity interventions for reducing burdens of infection, antibiotic use and antimicrobial resistance in animal agricultural settings - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
The review was published. The authors conclude that the paucity of studies evaluating structural interventions needs to be addressed and they propose the 'A' in WASH represent both 'Animals' and 'Air' in recognition of pathways of infection that can be addressed to also impact antimicrobial resistance (AMR).